E-Waste Recycling in Delhi NCR - Mrs. Deepika,; Dr. Mayank Jindal, (International Journal of Engineering and Management Research, 2024)
When an electronic product is thrown away after its useful life is over, it produces electronic trash, or e-waste. E-waste is produced in vast quantities as a result of the consumption-driven society and the quick development of technology. Recycling is the systematic gathering and treatment of items that would otherwise be discarded as waste, with the purpose of transforming them into fresh goods. Recycling can have positive impacts on your neighborhood, the economy, and the environment. The main objective of this paper is to describe the waste recycling companies in India. One primary motivation for recycling is to reduce expenses associated with waste collection and waste management. This also aids in mitigating the adverse environmental consequences of landfill garbage. To achieve the objective of this paper we have analyzed two big companies. In the analysis we have taken the company’s introduction, their founder and location, type of waste they are recycling and products they are producing.